Cell adhesiveness is related to tumorigenicity in malignant lymphoid cells (The Rockefeller University Press, 1984)
Mouse lymphoma cells (S49) that grow in suspension culture were selected for increased tumorigenicity through continuous passages in syngeneic BALB/c mice. Developing tumors were classified as high grade malignant lymphoma, small noncleaved type. Variants were selected from these tumorigenic cells that were able to grow as a monolayer attached to their substrate, resembling, in this respect, fibroblastoid cells. Whereas the tumorigenic suspension-growing parental cells were able to induce progressive tumors with an inoculum as low as 100 cells per mouse, the adherent cells were unable to develop as tumors even at an inoculum of 1 X 10(8) cells per mouse. In addition, mice inoculated once with live adherent cells were immunized against 1 X 10(7) suspension-growing cells. Involvement of an immune response in the rejection of tumorigenic S49 cells was suggested by (a) adoptive transfer experiments in which spleen cells from immunized mice protected naive mice and (b) the appearance of antibodies in the sera of immunized syngeneic mice that specifically recognized both adherent and suspension-growing S49 cells and detected differences in [35S]methionine-labeled antigens from these cells. Antibodies raised in rabbits against adherent cells recognized three proteins of 34,000, 61,000, and 72,000 apparent molecular weight in radiolabeled adherent cell extracts that are either absent or present in small amounts in extracts of suspension-growing tumorigenic S49 cells. These findings, taken together with our previous report (Hochman, J., A. Katz, E. Levy, and S. Eshel, 1981, Nature (Lond.), 290:248-249), suggest the S49 system as a novel system for studying growth control in malignant lymphoid cells.